From the analysis of teaching activity in situation to the contextual organizers of the activity: an approach through professional didactic - Magendie, Elisabeth (Swiss Journal of Educational Research, 2019)
Through this contribution, we show how we are participating in efforts to understand the interrelationships between teachers’ behaviors and certain contextual elements that are difficult to access, which organize their activity. More specifically, we report on the approach we have used to identify the contextual organizers of teaching activity. First, we present the theoretical and methodological tools that we use in our research, focused on the analysis of the activity of PSE trainees, to understand conceptualization processes. We then explain the method we use to highlight the contextual organizers, which orient and guide their activity. Finally, for illustrative purposes, we present some results that can be obtained by using this approach and highlight its relevance for the training of trainees.